ANALISIS MANAJEMEN PENGELOLAAN LIMBAH MEDIS B3 DI RUMAH SAKIT UMUM DAERAH (RSUD) PADJONGA DG. NGALLE KABUPATEN TAKALAR 2023 - Westy Tenriawi (Melati Institute, 2023)
Environmental health efforts play an important role in supporting the success of public health development. In accordance with the provisions of Law Number 36 of 2009 concerning Health, environmental health efforts are aimed at realizing the quality of a healthy physical, chemical, biological, and social environment that enables everyone to achieve the highest degree of health. Medical waste generated by health services is 10-25% and the remaining 75-90% is domestic waste. This type of research is descriptive research using qualitative methods. Supporting data were obtained from interviews, observations, and document reviews. The research was conducted at the Regional General Hospital H.Padjonga Dg.Ngalle Takalar Regency. B3 waste comes from medical service and support activities. Hazardous waste management at the hospital includes sorting, packaging, collection and storage. Transportation and processing are handed over by third parties, while for liquid B3 waste is put into the Waste Water Treatment Plant (WWTP) in the hospital except oil. The condition of hazardous solid waste management in the hospital has been running well but has not been optimized. Recommendations to improve or optimize hazardous waste management at H.Padjonga Dg.Ngalle Hospital, Takalar Regency include providing brown plastic bags to accommodate chemical and pharmaceutical waste, should create a special area for transporting hospital hazardous waste to avoid paths that are traversed by many people and should provide hepatitis immunization to cleaning services involved in handling hazardous waste to avoid the risk of infection in the event of a work accident.